Evaluation of the Implementation of the Reading Literacy Program at SD Negeri 100190 Tarutung Bolak - Siregar, Rahmat Sapaat (Journal of Indonesian Primary School, 2025)
The purpose of this study is to evaluate the implementation of the reading literacy program at SD Negeri 100190 Tarutung Bolak using a qualitative evaluative approach. Data was collected through participatory observations, in-depth interviews, and documentation involving principals, teachers, students, and parents. The findings of the study show that literacy programs have been carried out regularly through reading activities for 15 minutes before lessons, provision of reading corners in the classroom, and visits to school libraries. Strategies used by teachers, such as the use of reading and storytelling passports, have been successful in increasing student participation. School principals provide policy and infrastructure support, while parents begin to show involvement by providing reading support at home. Despite these successes, other challenges were encountered such as: limited collection of interesting books, lack of librarians, and uneven motivation of students. This program has had a positive impact on students' interest and reading ability, and has begun to build a strong literacy culture in the school environment. These findings are also in line with Vygotsky's theory of functional literacy and socio-cultural approach which emphasizes the importance of using routine and social interaction in the development of children's literacy.